National Evaluation of the Arrest Policies Program Under the Violence Against Women Act (VAWA), 1996-2000 - Archer, Cassandra ([Verlag nicht ermittelbar], 2003)
This study was undertaken to evaluate the impact of the Arrest Policies Program, funded by the Violence Against Women Office (VAWO), on criminal justice system changes and offender accountability, and victim safety and well-being. Through convenience sampling, six project sites were chosen to participate in the study. Part 1, Case Tracking Data, contains quantitative data collected from criminal justice agencies on arrests, prosecution filings, criminal case disposition, convictions, and sentences imposed for intimate partner violence cases involving a male offender and female offender. Data for Part 2, Victim Interview Data, were collected from in-depth personal interviews with domestic violence victims/survivors (1) to learn more about victim experiences with and perceptions of the criminal justice response, and (2) to obtain victim perceptions about how the arrest and/or prosecution of their batterers affected their safety and well-being. The survey instrument covered a wide range of topics including severity and history of domestic violence, social support networks, perceptions of police response, satisfaction with the criminal justice process and the sentence, experiences in court, and satisfaction with prosecutors, victim services provider advocates, and probation officers.